PENGEMBANGAN BAHAN AJAR E-BOOK PRAKTIKUM AKUNTANSI LEMBAGA/INSTANSI PEMERINTAHAN BERBASIS ANDROID DENGAN PENDEKATAN PROBLEM BASED LEARNING SEBAGAI SUMBER BELAJAR ALTERNATIF - Multiana, Ayun; Bahtiar, Moh. Danang (PENDIDIKAN SAINS DAN TEKNOLOGI, 2025)
The achievement of learning objectives is supported by using appropriate teaching materials. E-books, a type of digital teaching material that utilizes technology in the field of education, can be used as an alternative to improve learning outcomes. This study aims to create an android-based teaching material product using a problem-based learning approach (Problem-Based Learning) for accounting practicum material for government institutions or agencies, analyze whether teaching materials are feasible to use, and analyze how students respond to the teaching materials developed. The type of research used is the R&D (Research and Development) model with the 4D model developed by Thiagarajan, Semmel, and Semmel. This model consists of four stages: defining, designing, developing, and disseminating." There was no dissemination stage in this study due to researcher limitations. Quantitative and qualitative analysis were used to classify different types of data. The results showed that the criteria obtained were very feasible based on the average results of the feasibility of the material, linguistic, and graphical aspects of the experts' validation. The results of product trials on students in class XI of Financial and Institutional Accounting Vocational Schools reached very well-understood criteria.